Prevalence of Parkinson's disease: a population‐based study in Portugal. (2nd March 2017) - Ferreira, J. J.; Gonçalves, N.; Valadas, A.; Januário, C.; Silva, M. R.; Nogueira, L.; Vieira, J. L. M.; Lima, A. B.
Abstract : Background and purpose: Portugal has been identified as one of the countries with a high prevalence of LRRK2‐G2019S, considered to be the most frequent known cause of familial and sporadic Parkinson's disease (PD). The aim of this study was to evaluate the prevalence of PD in Portugal using a door‐to‐door methodology. Methods: A cross‐sectional study was conducted in the Portuguese community‐dwelling population; that is, elderly people living in the community on their own, aged ≥50 years and resident in mainland Portugal, in two phases: (i) a questionnaire was applied to screen potential cases of PD; and (ii) screened cases were evaluated by an expert in PD to confirm diagnosis. Results: The adjusted prevalence of PD for the Portuguese community‐dwelling population aged ≥50 years was 0.24%. The estimated total number of cases of PD for the Portuguese population is 180/100 000 inhabitants. Conclusions: The results of this study show that a geographical region with a high frequency of a causal mutation for PD does not automatically imply a high prevalence of patients with PD.